Water and Sediment Quality at Batang Baleh River - Jagath Retchahan, Sivalingam (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study was performed to determine the water and sediment quality of Batang Baleh River. The samplings were conducted at Batang Baleh River, Kapit during the month of August from 6th August till 8th August 2014 and from 12th February till 13th February 2015. In-situ data was collected from 10 stations and subjected to analysis according to Standard and Hach methods. Total suspended solids ranged from 1.7–104.17 mg/L and all the stations has been classified under Class I except stations 3, 8, and 9 which has been classified under Class II. BOD5 is classified as Class III for all the stations except for 1, 8, and 10 which has classification of Class II. For stations after the rain dissolved oxygen ranged from 6.27-7.72 mg/L and all the stations were classified under Class II. DO have increased slightly due to better oxygen solubility of fast flowing stream. TSS (2-185 mg/L), turbidity (1.53-1000 NTU) and after the rain stations were classified under Class III and above. The rise in TSS value after the rain is due to clay, silt, livestock runoff. Nutrients shows an increase in value due to nutrient in runoff. Particle size analysis shows mostly sandy type of soil texture. Based on the Water Quality Index (WQI), all the rivers were classified as Class II level except for station 7 after rain which shows Class III level. In conclusion, the rivers are clean and anthropogenic activities such as farming and logging has impact on river water and sediment quality